Gonom egow (where are you going?) - Retonel, Maricar A. 1990- (2014)
"By showing snippets of details of a life of a T'Boli girl, Gonom Egow aims to show a glimpse of the current status of T'boli people, especially the T'Boli youth, as they face a limbo between preserving their identity and culture and heading towards an imerging need of 'modernization' in Lake Sebu, Koronadal City, South Cotabato in Mindanao. The film wants to post a question: "Where is the T'Boli identiy is heading?". Could it be that these rich culture will be just seen and continuously 'hanging' on the museums or sold on botiques? George Mead's "Symbolic Interactionism" is the theoretical framework that makes this film stand. This theory helps explain the impact of the society towards building up self and how the self contribute to the society."